“In the end it is all about the people”: The importance of informal and nonformal education for marginalized groups in Kreis Bergstrasse - Chin-Kon Sung,Lotte Amber (2025)
Given the current societal and political developments in Germany, the visibility and integration of-marginalized is essential to ensure their inclusion in mainstream society. One way of encouraging-contact between majority and marginalized groups is through building social networks, of which-informal and nonformal educational activities play an important part. This thesis examines the-experience of marginalized people with informal and nonformal educational offers in Kreis Bergstrasse,-Germany using an autoethnographic approach.Kreis Bergstrasse is a relatively rural region in the middle of Germany. The main aim of this-research is to understand how informal and nonformal educational offers support the inclusion of-marginalized groups in society in Kreis Bergstrasse. It does so by applying a feminist GIS framework,-which strives to combine feminist methods with the traditionally more positivist GIS methods. By-interviewing 26 individuals who self-identify as marginalized this research understands where these-people find community and how they experience living in Kreis Bergstrasse. These findings are-presented in a textual and cartographic format to visually represent where people spend time and how-they feel about those places.The findings highlight the disparity between the visible promotion of informal and nonformaleducation and the places that are visited and valued by marginalized groups in society compared to the-offer for the broader population. The contextualization of the research in Kreis Bergstrasse shows that-regional differences regarding the offer and attendance of informal and nonformal education persist-within an administrative boundary. It also emphasizes how different types of marginalization are viewed-differently in society and the impact this has on the participation in informal and nonformal education.The research participants indicated a need for a central information point to find information on the-available educational offers in Kreis Bergstrasse. The maps resulting from the interviews can function-as such information point, which transcends language barriers and can encourage people to find-community in educational places.This research contributes to the existing literature on informal and nonformal educationexplicitly for marginalized groups and highlighting their individual challenges. Moreover, it shows the-practical needs of applying feminist GIS as a method and a concept to improve the visibility of-marginalized people in a cartographic way. Due to its practical applications, this research can aid policy-makers and other local stakeholders in Kreis Bergstrasse to optimize the information flows on and offers-of informal and nonformal educational events within the region leading to a more inclusive society.
Keywords: Feminist GIS; informal and nonformal education; marginalized groups; place attachment